A Peruvian Child with 18p-/18q+ Syndrome and Persistent Microscopic Hematuria - Poterico, Julio A.; Vásquez, Flor; Chávez-Pastor, Miguel; Trubnykova, Milana; Chavesta, Félix; Chirinos, Jenny; Salcedo, Nancy; Mena, Rosmery; Cubas, Sulema; González, Rocío; Alvariño, Rossana; Abarca-Barriga, Hugo (Journal of Pediatric Genetics, 2017)
Chromosome 18 pericentric inversion carriers could have offspring with recombinant chromosomes, leading to patients with clinical variable manifestations. Patients with 18p-/18q+ rearrangements share some clinical characteristics, while other characteristics differ. Factors for such divergence include the length of the inverted segment, among others. Here, we describe a Peruvian child with dysmorphic features, intellectual disability persistent microscopic hematuria, aortic pseudocoarctation, and descending aorta arteritis, among others. Karyotype analysis of family members determined the mother as the carrier of a pericentric inversion: 18[inv(18)(p11.2q21.3)]. This child carries a recombinant chromosome 18, with chromosomal microarray analysis detecting two genomic imbalances in patient's chromosome 18: one duplicated region and one deleted segment in the large and the short arms, respectively. Persistent microscopic hematuria has not been reported among 18p-/18q+ phenotypes. Our patient elucidates that other factors play significant and yet unknown roles for not fulfilling the proposed genotype–phenotype correlation associated with hemizygosity in this type of recombinant chromosome 18 or presenting these features as the patient ages.
Keywords: chromosome 18 pericentric inversion; recombinant chromosome 18; hematuria; microarray analysis; genotype–phenotype correlation